حديث ابن مسعود (في وصف الصراط المستقيم): « خط لنا رسول الله صلى الله عليه وسلم خطا، وقال: هذا سبيل الله ثم خط خطوطا عن يمينه وعن يساره... ». (دراسة حديثية نقدية) - عبدالله, أ.م.د. محمد حسين; كريم, سه روه ر سلام (Sulaimani Journal for Humanities, 2023)
Science is useful by graduating and studying hadith as one of the most important and greatest types of hadith sciences, because with this science it distinguishes the correct from the sick and the return from the acceptable, and it is the subject of ijtihad among the scholars. One of the best interpretations of the Holy Qur'an is the interpretation of the maxim, including the interpretation of the purified Sunnah, it is the best statement and interpretation. This research came to highlight and indicate the scientific personality of one of the prominent Kurdish scholars in the field of interpretation (the Holy Qur'an) in his printed interpretation and called B) good statement in the interpretation of the Holy Qur'an (by Sheikh Muhammad Taha Al-Balisani (d.: 1415 AH, 1995 AD) (may God have mercy on him).